Burden of Proof Reversal in Criminal Acts of Money Laundering - Syukri Akub; Andi Muhammad Sofyan; Fauzi Zainal, Muhammad Khusnul (Faculty of Law, Mulawarman University, 2019)
This study aims to analyze the burden of proof reversal system in handling cases of money laundering. This type of research is normative juridical legal research. The results of this study indicate that in the reversal system of the burden of proof of criminal acts of money laundering, each party has a burden of proof, the public prosecutor is burdened to prove that these assets are the property of the defendant and has a relationship with the original criminal act charged, while the defendant burdened to prove the origin of the assets claimed and if the defendant is unable to prove the origin of the assets, the assets can be strongly suspected to originate from criminal offenses. There are still obstacles in law enforcement both from the substance of the law (norms), legal structure (law enforcement agencies) and the culture of law (the culture of community law).